The display of photographic-quality images on the Web a comparison of two technologies. - Jao, C.S (IEEE Transactions on information technology in biomedicine)
Downloading medical images on the Web creates certain compromises. The tradeoff is between higher resolution and faster download times. As resolution increases, download times increase. High-resolution (photographic quality) electronic images can potentially play a key role in medical education and patient care. On the Internet, images are typically formatted as Graphics Interchange Format (GIF) or the Joint Photographic Experts Group (JPEG) files. However, these formats are associated with considerable data loss in both color depth and image resolution. Furthermore, these images are available in a single resolution and have no capability of allowing the user to adjust resolution as needed. Images in the photo compact disc (PCD) format have higher resolutions than GIF or JPEG, but suffer the disadvantage of large file sizes leading to long download times on the Web. Furthermore, native Web browsers are not currently able to read PCD files. The FlashPix format (FPX) offers distinct advantages over the PCD, GIF, and JPEG formats for display of high-resolution images on the Web. A Java applet can be easily downloaded for viewing FPX images. FPX images are higher resolution than JPEG and GIF images. FPX images offer rich resolutions comparable to PCD images with shorter download times.